Implementasi program pembelajaran calistung pada peserta didik kelas II di MI Salafiyah Tanon - Rahmawati, Diah Sekar; Utami , Novia Rahma Rista; Mashuri , Anwas (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
Reading, writing, and arithmetic (calistung) are fundamental skills that every individual must possess in order to recognize letters and numbers. The problem of calistung learning can be found in elementary school students, especially in lower grades. This research employs a descriptive qualitative research method. The research instruments consist of interviews and observation sheets. The data analysis technique in this research utilizes the Miles and Huberman model. The aim of this research is to enhance the calistung abilities of second-grade students at MI Salafiyah Tanon. This research focuses on the implementation of calistung learning programs, including planning, implementation, obstacles, and evaluation. Additionally, this research also discusses the positive and negative impacts of the calistung learning program conducted at MI Salafiyah Tanon.